A quality control model for the development of high-confidence flotation test data - Lotter, Norman Owen (Department of Chemical Engineering, 2016)
This thesis addresses the problem of obtaining reliable laboratory scale flotation test data for the Merensky ore type found in the Bushveld complex of South Africa. The complex nature of the platinum-group element (PGE) deportment in this ore renders the normally-practiced procedures inappropriate for this particular testwork. A more robust and thorough procedure is necessary because of the diverse mineralogical forms in which the PGE are found. The evaluation of the mass and value balances has accordingly to take these factors into account. The major features of the evaluation of input and output errors across the laboratory scale flotation test are analysed. It is found that unless size-by-size variance of PGE in a conventionally crushed mill feed is taken into account the mill feed sample size is underestimated by some 176%. Further the preparation of a reference distribution of assayed head material is necessary to provide the 95% confidence limits of grade estimate. The need for repeating flotation tests and compositing the adjudicated products is discussed, concluding that quintuplicates are suitable to achieve a desirable level of confidence in the built-up head grade. The sample preparation of the flotation products has a critical role in minimising evaluation errors, as is the case with fire assaying of samples where minimum numbers of replicate determinations have been calculated. An outlier rejection model for adjudication of the replicate built-up head grades is proposed, and a complete flowsheet of the quality control model is developed from first principles. The effect of this model on the PGE total balance is analysed. It is concluded that workable controls are defined, since a metal balance with < 1% error has been achieved.